The monitoring role of pension fund ownership in ESG firm controversies - Mercedes Alda (Borsa İstanbul Review, 2025)
This study examines the role of pension fund ownership as a control mechanism of ESG firm controversies. Institutional investors are traditionally considered passive owners; however, the role of pension funds is not clear because, in theory, they may be effective monitors as pressure-resistant investors. This work analyses the impact of UK equity pension funds on their investee firms' ESG controversies. The results indicate that a larger pension fund shareholding reduces controversies related to environmental and product responsibility areas. However, pension funds are passive monitors in other areas, such as workforce, to avoid conflicts of interest with company management. Moreover, we first consider the impact of social investment networks on ESG firm controversies, and the findings reveal that pension funds have diverse interests, especially conventional funds, which produces conflicts of interest in the networks. In addition, ambiguous information flows across the networks, leading to different interpretations of the information and thus diverse monitoring decisions regarding ESG firm controversies. Finally, pension fund shareholding encourages some substantive CSR engagement practices in the corporate citizenship area.
Keywords: 330; CSR engagement; ESG controversy; Investee firm; Network; Pension fund